Manajemen risiko pada lembaga keuangan syariah dalam menghadapi risiko operasional di era digital - Azis, Abd (Maliki Interdisciplinary Journal, 2026)
The development of the digital era has brought significant changes to the operations of Islamic financial institutions (IFIs) in Indonesia. On the one hand, digitalization opens up opportunities for efficiency and service expansion; on the other hand, it introduces new, more complex operational risks. This study aims to analyze the application of risk management in Islamic financial institutions in facing operational risks in the digital era and identify appropriate strategies to minimize these risks in accordance with Sharia principles. The discussion covers basic risk management concepts, types of digital operational risks, regulatory frameworks, mitigation strategies, and the integration of Sharia values into risk governance. The study results indicate that Islamic financial institutions need to adopt a comprehensive, technology-based risk management approach that aligns with the maqasid of Sharia to survive and thrive amidst the digital dynamics.